Sites of memory, sites of mourning and history : Danticat's insights into the past - Vega González, Susana (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
Memory has undoubtedly played a crucial role in the postmodern literary discourse. The dismantling of a monolithic, static and unquestioned history has given place to the predominance of a revisionary narrative impulse to “historicize the event of the dehistoricized” in Homi Bhabha’s terms. Haitian-American writer Edwidge Danticat joins the number of contemporary authors who are determined to uncover and recover the forgotten and manipulated histories of the dead. Taking the Massacre River dividing Haiti and the Dominican Republic as a site of memory as well as a site of mourning, Danticat writes The Farming of Bones (1998) as a tribute to those nameless and faceless who died victims of the abuses of power and racial persecution, providing them with names and voices against silence and oblivion. It is my aim to analyze the dimension of the use of memory in Danticat’s novel, especially in relation to the workings of history. Issues of power and racial oppression will be especially relevant in this analysis.